The Influence Of Leadership Style And Teamwork On The Performance Of Police Officers In The Criminal Investigation Unit Of The South Bengkulu Police - Ilkham Arisetyawan; Ahmad Soleh; Nurzam Nurzam (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
The purpose of this study is to determine the influence of leadership style and teamwork on the performance of members of the Criminal Investigation Unit of the South Bengkulu Police. The sample in this study was 36 members of the Bengkulu Selatan Police Criminal Investigation Unit. The results of the multiple linear regression analysis are the equation: Y = 11.579 + 0.404 X1 + 0.338 X2 + e, this illustrates a positive regression direction, meaning that the variables Leadership Style (X1) and Teamwork (X2) have a positive influence on Employee Performance (Y) in the Bengkulu Selatan Police Criminal Investigation Unit, Bengkulu Selatan. The magnitude of the coefficient of determination from the calculation results using SPSS can be seen from the coefficient of determination of R square of 0.690. This means that the value of Leadership style (X1) and teamwork value (X2) affect member performance (Y) by 69% while the remaining 31% is influenced by other variables not examined in the study. The results of the t test at a significance level of 0.05 explain that partially Leadership style and teamwork have a significant influence on member performance in the police members of the South Bengkulu Regency Criminal Investigation Unit. T count in the study that the variables of leadership style and teamwork are 3.333 and 3.208 which means more than t table which is 2.029.